Optimal Management of Upper Tract Urothelial Carcinoma: Current Perspectives - Leow, Jeffrey J (Onco Targets Ther, 2020)
INTRODUCTION: Upper tract urothelial carcinoma (UTUC) is a relatively uncommon urologic malignancy for which there has not been significant improvement in survival over the past few decades, highlighting the need for optimal multi-modality management. METHODS: A non-systematic review of the latest literature was performed to include relevant articles up to June 2019. It summarizes the epidemiologic risk factors associated with UTUC, including smoking, carcinogenic aromatic amines, arsenic, aristolochic acid, and Lynch syndrome. Molecular pathways underlying UTUC and potential druggable targets are outlined. RESULTS: Surgical management for UTUC includes kidney-sparing surgery (KSS) for low-risk disease and radical nephroureterectomy (RNU) for high-risk disease. Endoscopic management of UTUC may include ureteroscopic or percutaneous resection. Topical instillation therapy post-KSS aims to reduce recurrence, progression and to treat carcinoma-in-situ; this may be achieved retrogradely (via ureteric catheterization), antegradely (via percutaneous nephrostomy) or via reflux through double-J stent. RNU, which may be performed via open, laparoscopic or robot-assisted approaches, is the gold standard treatment for high-risk UTUC. The distal cuff may be dealt with extravesical, transvesical or endoscopic techniques. Peri-operative chemotherapy and immunotherapy are increasingly utilized; level 1 evidence exists for adjuvant chemotherapy, but neoadjuvant chemotherapy is favored as kidney function is better prior to RNU. Immunotherapy is primarily reserved for metastatic UTUC but is currently being investigated in the perioperative setting. CONCLUSION: The optimal management of UTUC includes a firm understanding of the epidemiological factors and molecular pathways. Surgical management includes KSS for low-risk disease and RNU for high-risk disease. Peri-operative immunotherapy and chemotherapy may be considered as evidence mounts.